ChemInform Abstract: Ru(II)‐Catalyzed Intermolecular ortho‐C—H Amidation of Aromatic Ketones with Sulfonyl Azides. Issue 38 (30th August 2013) - Bhanuchandra, M.; Yadav, M. Ramu; Rit, Raja K.; Kuram, Malleswara Rao; Sahoo, Akhila K.
Abstract The Rh(II)‐catalyzed amidation of ketones (I) with tosyl azide leads to ortho‐amidated derivatives (III) as single products.